Geographic variation in phenology behavior and response to drought of cork oak populations is crucial to cope with climate change - Rodrigues, Ana Paula (2013)
Cork oak is widely distributed in the Western Mediterranean region, spanning a range of different environmental conditions, and frequently dominating open woodlands of high conservation and socioeconomic value. Cork oak woodlands spread-out for over 715000 ha in Portugal, covering 21% of the national forested area and 30% of the world’s cork producing area. Cork oak is well adapted to the seasonal drought of Mediterranean climate, following several decades of warming- up and frequent drought years. However, since the 70's, maximum and minimum temperatures have risen in Portugal about 0.5 ºC each decade, corresponding to twice the average world temperature increment. In addition, since longer, more frequent, and more intense drought periods are expected, stress caused by the expansion of arid and semi-arid climate throughout the country will affect the species distribution. Consequently, not only established stands may be prone to tree mortality, but also the current reforestation effort may be jeopardized by low survival rates attributed to the use of unsuitable genetic material. It is expected that, through genetic adaptation and/or phenotypic plasticity, cork oak populations may have developed significant differences in fitness and the traits related to it. In this context, provenance trials are the best resource of material to assess the variability between and within populations from seed sources sampled in a wide range of locations (stands) covering the geographical distribution of the species. This will enable to assess the levels and patterns of genetic variation for growth and traits determining adaptation to a specific environment, hence providing crucial information to select appropriate seed sources for planting, as well as to develop sustainable breeding and gene conservation programs. In 1998, multi-site provenance trials were established at three locations in Portugal, as a part of the “European Network for the Evaluation of Genetic Resources of Cork Oak for Appropriate Use in Breeding and Gene Conservation Strategies”. Results from these field trials at 7 years from planting pointed out that seed origin must be considered in reforestation programs, since survival, growth and adaptive traits (phenology, water use efficiency - wue) showed significant differences among populations. Responses to drought (a major limitation to cork oak regeneration) of four contrasting populations, selected according to their field performance for growth, phenology and wue, were further studied under controlled-environment conditions where drought stress was induced. In addition, morphological (total height, root/shoot biomass), physiological (wue, water potential, relative water content and gas exchange) and biochemical (maximum quantum yield of PSII) traits were assessed in 6-month seedlings produced from acorns collected in the stands representing the four contrasting provenances. Results from the controlled experiment provided an indication that drought adaptation was mainly related to early stomatal closure and root investment, with these traits showing significant differences between the studied populations. We have also observed significant differences in growth rhythm, as well as dissimilar temporal drought responses, in the populations under study. In conclusion, both field trials and controlled environment showed consistent results and indicated an important influence of geographic origin on growth performance and wue.